Comparison of oxidized/nitrided Zr thin films on Si and SiC substrates - Wong, Y.H.; Cheong, K.Y. (Elsevier, 2013)
This work utilizes simultaneous thermal oxidation and nitridation technique to transform sputtered Zr to ZrO2 and to Zr-oxynitride thin films on Si and SiC substrates, respectively, in nitrous oxide gas ambient. Various characterization techniques such as X-ray photoelectron spectroscopy, energy-filtered transmission electron spectroscopy, atomic force microscopy, X-ray diffraction, capacitance–voltage measurements, and leakage current density-electric field measurements were carried out to evaluate and compare the structural, chemical, and electrical properties of the films produced on both Si and SiC substrates.